Foundational Skills : Phonics for Pre-Kindergarten. - Education, Shell (Foundational Skills: Phonics Ser., 2013)
Support students' phonetic development as they practice key pre-kindergarten phonics skills. Focus on phonics with fun and engaging activity pages that are research based and support the Common Core State Standards.